The location of emotional intelligence measured by EQ-i in the personality and cognitive space: Are there gender differences? - Tommasi, Marco; Sergi, Maria Rita; Picconi, Laura; Saggino, Aristide (Frontiers in Psychology, 2023)
Introduction Emotional Intelligence (EI) is first described by Salovey and Mayer as the ability to perceive and understand emotions and the ability to use them as supports for thoughts. Despite the great notoriety of EI, its definition remains not completely clear. An operative definition of EI can be achieved by studying its connection with other individual characteristics such as gender, personality traits, and fluid intelligence. Methods The sample was composed of 1,063 Italian subjects. A total of 330 participants were employed (31.0%; 57.9% men) and 702 were university students (66.0%; 38.7% men). The Emotional Quotient Inventory (EQ-i), one of the most used questionnaires in literature, was used to measure EI. The exploratory structural equation modeling (ESEM) was used to assess the role of personality traits (five-factor model of personality) and fluid intelligence in EI. Statistical analyses on differences between men and women means of total and subscale EQ-i scores were estimated to evaluate whether EI, measured by EQ-i, is influenced by gender. Furthermore, a Multigroup Confirmatory Factor Analysis was conducted to assess measurement invariance in relation to gender groups. Results Emotional Intelligence, measured by EQ-i, is prevalently connected with personality traits rather than fluid intelligence. Furthermore, men outperformed women in the Intrapersonal and Stress Management EI factors, and women outperformed men in the Interpersonal EI factor. No difference in the means of the EI total score and EI latent general factor did not differ between gender groups. Conclusion Emotional Intelligence, measured by EQ-i, can be conceptually considered as a Trait EI. Furthermore, men are more capable to cope with negative events and to control impulses, while women are more able to distinguish, recognize, and comprehend others’ emotions.